Tailored enzymes as next-generation food-packaging tools. Issue 8 (August 2022) - Sharma, Vivek K.; Sharma, Minaxi; Usmani, Zeba; Pandey, Ashok; Singh, Brahma N.; Tabatabaei, Meisam; Gupta, Vijai Kumar
Abstract : Enzymes have the potential for biotransformation in the food industry. Engineering tools can be used to develop tailored enzymes for food-packaging systems that perform well and retain their activity under adverse conditions. Consequently, novel tailored enzymes have been produced to improve or include new and useful characteristics for intelligent food-packaging systems. This review discusses the protein-engineering tools applied to create new functionality in food-packaging enzymes. The challenges in applications and anticipated directions for future developments are also highlighted. The development and discovery of tailored enzymes for smart food packaging is a promising way to ensure safe and high-quality food products. Highlights: Protein-engineering tools for the discovery of next-generation enzymes could meet the demand for newer classes of food-packaging systems. Novel tailored enzymes can be produced to improve or include new and useful characteristics for intelligent food-packaging systems. Protein-engineering tools could also be used to create new functionality in food-packaging enzymes. Tailored enzyme-based food packaging is a promising way to fulfill consumers' desires for safe and high-quality food products.